Influence of 50-Hz Electromagnetic Field on Anurian (Xenopus laevis) Metamorphosis - S. Grimaldi; A. Lisi; S. Reiti; V. Manni; M. Ledda; L. Giuliani (The Scientific World Journal)
In this study, we show the effect of a 1-mT magnetic field AC at 50 Hz on Xenopus laevis tadpole populations. In the course of a 65-day exposure to the field, tadpole survival showed a small, but significant, decrease (p < 0.0004), together with a striking parallel 6-day shift in tadpole maturation frequency and a significant impairment of their metamorphosis. Particularly, metamorphosis was successful for 85% of individuals in the unirradiated tadpole population and for 45% of individuals in the irradiated tadpole population, respectively.